[Ox Cart] - (:unkn) unknown (My University, 2010)
A man standing next to his oxen cart
Colour: Black and white; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Oxen--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; [1950]; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Hats--Trinidad and Tobago; Palms--Trinidad and Tobago; Roads--Trinidad and Tobago; Benches--Trinidad and Tobago; Rural transportation--Trinidad and Tobago; Transportation--Trinidad and Tobago